The Balance Sheet: the Main Financial Statement and its Informative Significance - Годек, Ян Веслав (Ekonomika, 1996)
In the market economy every company becomes more responsible for the results of the performance of the company. Financial statements in the company must be so informative that managers and other users of this statement are able to utilize them for making decisions and forcasting. The main statement of an annual financial report is the balance sheet and, therefore, scientists of various contries study conceptions of producing the balance sheet. This article is devoted to items of improvement of the balance sheet and making it more informative.